Identifikasi Kemampuan Argumentasi Mahasiswa Pendidikan Kimia Dalam Praktikum Kimia Analitik - Dwi Cahyati, Shellvia; Kriswantoro, Kriswantoro; Asrial, Asrial; Damris, Damris (JURNAL MANAJEMEN PENDIDIKAN, 2025)
IDENTIFICATION OF CHEMISTRY EDUCATION STUDENTS' ARGUMENTATION ABILITIES IN ANALYTICAL CHEMISTRY PRACTICESThis study aims to determine the argumentation skills of Chemistry Education students in Analytical Chemistry laboratory activities. The research employed both quantitative and qualitative approaches with a sample of Chemistry Education students. Data on argumentation skills were collected through post-test assessments and group discussions, then analyzed based on the categories of very high, high, moderate, low, and very low. The results showed that 18.18% of students had very high argumentation skills, 31.82% had high argumentation skills, 22.73% had moderate argumentation skills, 13.64% had low argumentation skills, and 13.64% had very low argumentation skills. These findings indicate a variation in students’ argumentation abilities, with the majority falling into the high category; however, some students still need to improve their argumentation skills. This study highlights the importance of implementing argumentation-based laboratory guides to foster the development of critical thinking and systematic argumentation skills among all students.